Effects of interactive learning module technology on Kazakh as a second language learners’ achievement and communication skills - Yermekbayeva, Gulmira; Kuzembayeva, Gulzhana; Maydangalieva, Zhumagul; Spulber, Diana (Journal of Education and e-Learning Research, 2024)
This study aimed to investigate the effectiveness of interactive learning module technology (ILMT) in teaching Kazakh as a second language in secondary schools in the Republic of Kazakhstan. This research was carried out at Russian-medium secondary schools during the academic year 2021-2022. There were two groups in the sample: the experimental (n=63) and control (n=61). The experimental group received an education based on the ILMT while the control group received an education based on the curriculum's traditional technique. The study used a mixed research design and was divided into two sections: quantitative and qualitative. A semi-experimental pre- and post-test control group design was adopted in the quantitative section. The qualitative section employed phenomenology. The quantitative data were acquired using the students' knowledge assessment test and analyzed using comparative analysis. An interview questionnaire and observations were used to obtain qualitative data which was then evaluated using content analysis. The experimental group outperformed the control group in terms of mean post-test knowledge assessment test scores. The ILMT in teaching Kazakh as a second language is efficient in improving the quality of mastering Kazakh language by Russian-speaking students. Content analysis showed that the ILMT helps to reduce students' anxiety and increase independence which is necessary for the development of students' communication skills.